Growth of gold-assisted gallium arsenide nanowires on silicon substrates via molecular beam epitaxy - Delos Santos, Ramon Mandapat (National Institute of Physics, College of Science, University of the Philippines Diliman, 2009)
Gallium arsenide nanowires with different diameters are grown on silicon (100) substrates by what is called the vapor-liquid-solid (VLS) growth mechanism using a molecular beam epitaxy (MBE) system. Good quality nanowires with surface densities of approximately 10^8 nanowires per square centimeter are produced by utilizing gold nanoparticles of different sizes, with densities of 10^11 nanoparticles per square centimeter, as catalysts for nanowire growth.